The Routledge handbook of forensic linguistics - Coulthard, Malcolm 1943-; May, Alison 1959-; Sousa-Silva, Rui (Routledge, 2021)
The language of the law and the legal process -- The linguist as expert in the legal process -- New directions -- Concluding remarks
Includes bibliographical references and index
Keywords: Forensische Linguistik; Forensic linguistics; Aufsatzsammlung